Optimalisasi Administrasi Sarana dan Prasarana untuk Mewujudkan Lingkungan Belajar yang Berkualitas - Fatimah, Meti; Sayidah, Aminatus; Faizi, Ahmad Akbar Al (Lembaga Yasin AlSys, 2026)
Facilities and infrastructure administration constitutes a strategic aspect in supporting the effective delivery of education and organizational performance, because well-managed facilities and infrastructure facilitate teaching and learning processes, enhance work efficiency, and create a safe and comfortable environment. This article aims to explain the urgency of facilities and infrastructure administration that is planned, well-organized, and sustainable, while also reviewing recurring practical challenges, including inadequate planning, discontinuous maintenance, and suboptimal utilization of facilities in relation to actual needs. The discussion emphasizes that facilities and infrastructure administration should encompass an integrated sequence of processes from planning, procurement, and distribution to maintenance and asset disposal—grounded in the principles of effectiveness and efficiency. This conceptual analysis indicates that systematic and professional management of facilities and infrastructure is an essential prerequisite for achieving educational goals, improving institutional service quality, and fostering more optimal and competitive learning processes.